The critical turn : rhetoric and philosophy in postmodern discourse - Angus, Ian H.; Langsdorf, Lenore, 1943- (Southern Illinois University Press, 1993)
Concerned with criticizing representational theories of knowledge by developing alternative concepts of knowing and communicating, Ian Angus and Lenore Langsdorf bring together eight essays that are united by a common theme: the convergence of philosophy and rhetoric. In the first chapter, Angus and Langsdorf illustrate the centrality of critical reasoning to the nature of questioning itself, arguing that human inquiry has entered a "new situation" where "the convictions and orientations that have traditionally marked the separation of rhetoric and philosophy -- the concern for truth and the focus on persuasion -- have begun to converge on a new space that can be defined through the central term discourse." In these essays, this convergence of rhetoric and philosophy is addressed as it presents itself to a variety of interests that transcend the traditional boundaries of these fields. -- Publisher description.